THE IMPACT OF E-COMMERCE IN ON-LINE BUSINESS - Kartika, Rayna (Jurnal Analisis Bisnis Ekonomi, 2008)
This research paper has aimed to-Commerce the first and the second waves, to find out the important role of E-Commerce in business, and to predict the future of E-Commerce. Those there issues will be the limination in this research paper. Since this is a literature analysis, it will have some critiques, extend, analysis, and review fromthe previous literature. In this research paper, there are some factors which contribute the success of E-Commerce including new business strategy, efficiency, and generating profits from new revenue models. The liminations of implementing E-Commerce are derived from technical and non-technical limination which can lead the failures ofE-Commerce. E-Commerce also plays a significant role for business to grow and develop, particularly, in maximizing profits and reducing costs. Hence, there are many strategies and new technologies offered by experts to implemen E-Commerce precisely. The growh of E-Commerce will lead to the prediction and speculation of how E-Commerce will be in the next future.